Effect of perioperative FLOT versus ECF/ECX on short-term outcomes after surgery for resectable oesophagogastric adenocarcinoma: propensity score-matched study. Issue 1 (23rd February 2022) - Moussa, Osama; Bhogal, Ricky Harminder; Malietzis, George; Fribbens, Charlotte; Starling, Naureen; Gerlinger, Marco; Watkins, David; Chau, Ian; Rao, Sheela; Cunningham, David; Allum, William H.; Chaudry, Asif; et al.
Abstract: Background: Perioperative FLOT (fluorouracil plus leucovorin, oxaliplatin, and docetaxel) chemotherapy is a recent regimen used to treat resectable oesophagogastric (OG) adenocarcinoma, associated with improved overall survival versus earlier chemotherapy strategies. This study compared short-term perioperative morbidity in a large tertiary centre series of FLOT to a matched cohort receiving ECX/ECF (epirubicin, cisplatin, capecitabine (X) or 5-fluorouracil (F)). Methods: Consecutive patients completing four perioperative cycles of FLOT and proceeding to surgery with resectable OG adenocarcinoma were included. This was matched to patients from a historic ECX/ECF cohort from the same institution. A propensity score was calculated, and a secondary analysis using a propensity-matched group performed. Results: Cohorts were matched by tumour location and operations performed. In total there were 129 (64.5 per cent) oesophageal and 71 (35.5 per cent) gastric resections (FLOT 57 oesophageal, 43 gastric; ECF/ECX 64 oesophageal, 36 gastric). The median length of stay after surgery was 12 days in the FLOT group versus 15 in ECF/ECX ( P = 0.035). There were no significant differences in overall perioperative complications and, specifically, no difference in OG anastomotic leaks, analysed by site (gastric (FLOT 0/79 (0 per cent) versus ECX 2/79 (2.5 per cent); P = 0.123), oesophageal (FLOT 4/121 (3.3 per cent) versus ECX 5/121 (4.1 per cent); P = 0.868) or type of surgery (open FLOT 1/121 (0.8 per cent) versus ECX 3/121 (2.5 per cent); P = 0.368; minimally invasive (FLOT 3/121 (2.5 per cent) versus ECX 2/121 (1.7 per cent); P = 0.555)). There was no statistical difference in leak-related return to theatre, 30-day (FLOT 0 (0 per cent) versus ECX 3/100 (3.0 per cent); P = 0.081), or 90-day (FLOT 0 (0 per cent) versus ECX 2/100 (2.0 per cent); P = 0.155) mortality. Conclusion: In terms of surgical complications, FLOT and ECX/ECF were equally safe in patients undergoing resection for OG adenocarcinoma. Abstract : A case-matched study comparing the perioperative outcomes of oesophagogastric adenocarcinoma in a single tertiary centre. There were no significant reported differences in perioperative complications between cohorts across all systemic classifications of benchmark complications.